Hypoglycemic effects of aqueous extract of Salvia mirzayanii Rech. F& Esfand in diabetic patients; a randomized controlled trial study - Soheila Moein; Paknoosh Saberi; Mahmoodreza Moein; Rahman Mehdizadeh; Mohammadmehdi Zarshenas (Society of Diabetic Nephropathy Prevention, 2020)
Introduction: Medicinal plants are used in diabetes treatment. Salvia mirzayanii Rech. F& Esfand was used for diabetes treatment in Iranian traditional medicine. Objectives: The main objective of this study is to investigate the antidiabetic effects of aqueous extract of S. mirzayanii in diabetic patients. Patients and Methods: In the present randomized controlled trial study, the patients were divided into trial (n=27) and control (n=25) groups. The trial group received daily one capsule containing 450 mg of aqueous extract of Salvia mirzayanii; the control group received daily one capsule containing 450 mg of caramelized flour and 5% aqueous extract of S. mirzayanii. Fasting blood samples were collected at the beginning of the study and after 3 months, fasting blood sugar (FBS), HbA1 C, insulin, HOMAIR index, alanine transaminase (ALT), aspartate transaminase (AST), and lipid profile were evaluated. Results: Types of used drugs, gender, age, and body mass index (BMI) were not significantly different between trial and control groups before treatment. Additionally, after treatment, BMI did not significantly change between these two mentioned groups. The results showed that FBS and HbA1 C levels did not change significantly in the trial group after treatment; however, in this group, insulin secretion was increased significantly (P=0.015). Nevertheless; after treatment, HOMA-IR index did not significantly change between the two mentioned groups. In the trial group, after treatment, liver enzymes (ALT and AST) levels did not change significantly. After the treatment, LDL-C was changed in the trial group. Conclusion: The herbal drug used in the present study enhanced insulin secretion, and improved LDL-C level in diabetic patients.